Agronomic Evaluation and Yield Potentials of Grafting of Piper nigrum and Piper colobrinum - Aini , Sitti Nurul; Kurniawati, Ani; Khodijah , Nyayu Siti; Fridahaqi, Rhaisyarara (Journal of Tropical Crop Science, 2024)
Foot rot disease (Phytophthora capsica) is Indonesia's primary challenge in cultivating pepper (Piper nigrum). Grafting to another Piper species, Piper coclobrinum, or melada (the local name), is a potential solution to increase resistance to this disease. The use of melada as rootstock has shown promising results during the seedling phase, but it has not been thoroughly evaluated during the production phase. The study was conducted in the pepper grower’s location in Puput and Simpang Katis Villages, Central Bangka, Bangka Belitung Islands Province. The study used kapok (Ceiba petandra) as the standard; plant morphology, leaf area, leaf thickness, and crown diameter for grafted melada and non-grafted pepper were recorded. Harvest variables included panicle length, panicle weight, the number of fruits per panicle, and fruit diameter, measured in three different areas of the canopy: the lower area (0-1 meter above the ground surface), the middle area (1-2 meters above the ground surface), and the top area (more than 2 meters above the ground surface). Physiological variables measured included rates of photosynthesis, stomatal conductance, transpiration rate, intercellular CO2, and CO2 conductance. The study demonstrated that the grafted pepper plants had a larger leaf area than the non-grafted pepper plants; the panicle weight and the number of fruits per panicle were higher. Panicles located in the middle zone of the plant canopy tended to be longer for grafted and non-grafted peppers. Panicle weight, fruit size, and the number of fruits per panicle were generally more significant at the top of the plant canopy. In all parts of the canopy, grafted peppers exhibited larger fruit size, greater panicle weight, and a higher number of fruits per panicle than non-grafted “Nyelungkup” peppers, highlighting the potential of melada as a rootstock for pepper plants.